Terrestrial Response to Maastrichtian Climate Change Determined from Paleosols of the Dawson Creek Section, Big Bend National Park, Texas - Anna K. Lesko; Steve I. Dworkin; Stacy C. Atchley (Geosciences)
Climate during the Late Cretaceous is characterized by a long-term cooling trend interrupted by several periods of increased warming. This study focuses on the terrestrial response to two rapid climate events just prior to the K-Pg boundary marked by the Chicxulub impact: the Mid-Maastrichtian Event (MME) and the Late Maastrichtian Warming Event (LMWE). These hyperthermals caused widespread biotic and greenhouse gas-related disturbances, and clarification about their timing and environmental character reveals the independent nature of all three events. Using element concentrations in bulk paleosols, as well as element concentrations in pedogenic calcite from paleosols in the Tornillo Basin of West Texas, we reconstruct mean annual precipitation (MAP) and the character of soil weathering across the K-Pg boundary. Modelled MAP indicates increased precipitation during the first half of the MME and rapid high amplitude changes in precipitation during the second half of the MME. The Tornillo Basin became increasingly dry during the LMWE followed by wet conditions that continued across the K-Pg boundary. This study documents the co-occurrence of sedimentation patterns, sea level change, and climate change caused by separate tectonic events prior to the K-Pg boundary.